THU0375 IMPROVEMENTS IN GLOBAL FUNCTIONING AND HEALTH-RELATED QUALITY OF LIFE AND THEIR ASSOCIATION WITH DISEASE ACTIVITY AND FUNCTIONAL IMPROVEMENT IN PATIENTS WITH ACTIVE ANKYLOSING SPONDYLITIS TREATED WITH UPADACITINIB: RESULTS FROM THE SELECT-AXIS 1 TRIAL. (2nd June 2020) - Kiltz, U.; Sieper, J.; Deodhar, A.; Zueger, P.; Song, I. H.; Chen, N.; Van der Heijde, D.
Abstract : Background: Upadacitinib (UPA) has been shown to be effective in patients with active ankylosing spondylitis (AS) [1]. However, improvements in global functioning and health-related quality of life (HRQoL) in these patients, and their relationship with established clinical response measures have not been fully characterized. Objectives: To evaluate the effect of UPA on the Assessment of SpondyloArthritis international Society Health Index (ASAS HI) and Ankylosing Spondylitis Quality of Life (ASQoL) questionnaire and quantify incremental improvements in ASAS HI and ASQoL response in patients achieving established AS disease activity and physical function improvements at Week (Wk) 14. Methods: This was a post-hoc analysis of the SELECT-AXIS 1 trial [1]. Patients received either UPA 15 mg once daily or placebo (PBO) for 14 wks. Mean change in ASAS HI and ASQoL from baseline (BL) to Wks 4, 8 and 14 for UPA and PBO were calculated and UPA vs PBO responses were compared. Changes in ASAS HI and ASQoL above the minimum clinically important difference (MCID ≥3-point improvement for both measures) and ASAS HI 'good health state' (ASAS HI score ≤5) at Wk 14 were determined. Changes from BL in ASAS HI and ASQoL were assessed within the combined UPA and PBO group reaching established improvement thresholds across AS clinical response measures (ASAS response criteria, ASDAS improvement criteria, and BASFI MCID) at Wk 14. Mean ASAS HI and ASQoL changes across groups within each measure and magnitude of ASAS HI and ASQoL change between responders and non-responders were compared. Results: UPA treatment resulted in significant improvement from BL in ASAS HI and ASQoL at Wk 14 with more patients achieving a MCID and ASAS HI good health state vs PBO (Table ). Significant improvements were observed earlier for ASAS HI than for ASQoL, starting at Wk 4. At Wk 14, achievement of clinical improvement thresholds was associated with increasing improvements in both ASAS HI and ASQoL scores (Figures 1 and 2). The magnitude of improvement between the best and worst response categories was greater for ASAS HI than ASQoL: 43-fold vs 7-fold for ASAS response, 5-fold vs 3.8-fold for ASDAS improvement, and 34-fold vs 10.4-fold for BASFI MCID achievement. Conclusion: UPA treatment in patients with active AS resulted in clinically meaningful improvements vs PBO in global functioning and HRQoL as measured by ASAS HI and ASQoL, with both measures showing discriminatory ability. Earlier UPA vs PBO response and greater magnitude of change across known clinical response groups suggests that ASAS HI may demonstrate greater responsiveness and ability to capture improvements in AS disease activity and physical function achieved with treatment. References: [1]van der Heijde D, et al. Lancet 2019;394:2108–17. Acknowledgments: Financial support for the study was provided by AbbVie. AbbVie participated in interpretation of data, review, and approval of the abstract. All authors contributed to development of the abstract and maintained control over final content. Medical writing services, provided by Joann Hettasch of JK Associates Inc., were funded by AbbVie. Disclosure of Interests: Uta Kiltz Grant/research support from: AbbVie, Amgen, Biogen, Novartis, Pfizer, Consultant of: AbbVie, Biocad, Eli Lilly and Company, Grünenthal, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Novartis, Pfizer, Roche, UCB, Joachim Sieper Consultant of: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Speakers bureau: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Atul Deodhar Grant/research support from: AbbVie, Eli Lilly, GSK, Novartis, Pfizer, UCB, Consultant of: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB, Patrick Zueger Shareholder of: AbbVie, Employee of: AbbVie, In-Ho Song Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., Naijun Chen Shareholder of: AbbVie Inc, Employee of: AbbVie Inc, Désirée van der Heijde Consultant of: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Cyxone, Daiichi, Eisai, Eli-Lilly, Galapagos, Gilead Sciences, Inc., Glaxo-Smith-Kline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, UCB Pharma; Director of Imaging Rheumatology BV